Pemodelan Simulasi Strategi Produktivitas Gerai Menggunakan Sistem Dinamik - Putri, Avistha Veradina (SM Institute, 2025)
The pandemic conditions have forced companies operating in the logistics sector to expand to increase their business due to the high surge in demand in the community. However, after the pandemic ends, companies must be able to maintain their business by implementing efficiency. There are many ways that companies can implement efficiency, in this research we will discuss how to implement cost efficiency in operations in branches in the Jakarta area using modeling simulations. This research is limited to costs that can be carried out by a budget system (excluding external factors, such as government policy, etc.). The simulation was carried out using historical company data and conducted interviews at several branches in the Jakarta area. The modeling was created using STELLA software and from several cost variables, what can be simulated is parking costs. The average total existing expenditure per month for all outlets in the Jakarta area is IDR 64,606,000 and after implementing the budget system, expenditure was reduced by 44.12% to IDR 25,050,000 with savings of IDR 39,556,000/month. If accumulated over a year, the total savings is IDR 474,672,000 Keywords : Operational Cost; Logistics; Modeling; Simulation; Dynamic System